Measurement of Aerosols and Trace Gases in the Free Troposphere at the Pico Mountain Observatory in the Azores. - Kramer, Louisa (2013)
European Geosciences Union (EGU), General Assembly. Viena, Austria, 07 - 12 April 2013.